2009
DOI: 10.1007/s12272-009-2010-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DNA topoisomerases I and II and cytotoxicity by lignans from Saururus chinensis

Abstract: Thirteen lignans, erythro-austrobailignan-6 (1), meso-dihydroguaiaretic acid (2), sauchinone (3), 1'-epi-sauchinone (4), saucerneol D (5), manassantin B (6), manassantin A (7), nectandrin B (8), machilin D (9), saucerneol F (10), saucerneol G (11), saucerneol H (12) and saucerneol I (13), were isolated from the ethyl acetate extract of the roots of Saururus chinensis. Among these compounds, 5 showed potent inhibitory activities against DNA topoisomerase I and II, and 5, 6, 7 and 10 showed mild cytotoxicities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The isolated lignans from S. chinensis and S. cernuus showed potential anti-inflammatory, anti-metastatic, neuroleptic, and cholesterol-lowering activities [15,16,[28][29][30][31][32][33]. Additionally, these compounds exhibited hepatoprotective, antifibrotic, antiseptic, antioxidative, anti-tumor DNA replication, and anti-HIV effects [2,4,[34][35][36]. Therefore, the Saururus species of plants may be useful in human diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolated lignans from S. chinensis and S. cernuus showed potential anti-inflammatory, anti-metastatic, neuroleptic, and cholesterol-lowering activities [15,16,[28][29][30][31][32][33]. Additionally, these compounds exhibited hepatoprotective, antifibrotic, antiseptic, antioxidative, anti-tumor DNA replication, and anti-HIV effects [2,4,[34][35][36]. Therefore, the Saururus species of plants may be useful in human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we reported on the isolation and cytotoxic activity of lignans from the roots of S. chinensis including four new lignans saucerneol F (SF) (Fig. 1), saucerneol G, saucerneol H, and saucerneol I [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…MB, a neolignan isolated from the roots of S. chinensis, has been demonstrated to exhibit a range of activities, including anti-inflammatory (10,(19)(20)(21), antiseptic (22) and antitumor activities (11,23). Furthermore, MB was shown to inhibit PMA-induced ICAM-1 expression in HL-60 cells (15) and to prevent monocyte adhesion to HUVECs through the inhibition of ICAM-1, VCAM-1 and E-selectin expression stimulated by TNF-α (24).…”
Section: Discussionmentioning
confidence: 99%
“…It has a long history of use in China as a folk medicine to remedy various edema, gonorrhea, jaundice and inflammatory diseases (9)(10)(11). Previous phytochemical and pharmacological studies on this plant have revealed several types of secondary metabolites, such as lignans, neolignans, aristolactams and flavonoids, as the biologically active compounds (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…7) Manassantin B (Man B) is a neolignan isolated from the roots of Saururus chinensis (S. chinensis) and has been reported to exert various biological activities, including antiinflammatory, 8,9) anti-septic, 10) anti-human immunodeficiency virus (HIV), 11) and anti-tumor activities. 12) In addition, Man B has been shown to inhibit hyperpigmentation and the expressions of adhesion molecules. 13,14) However, the effects of Man B on PGD 2 generation in mast cells have not been previously reported.…”
mentioning
confidence: 99%